2017
DOI: 10.1002/mus.25526
|View full text |Cite
|
Sign up to set email alerts
|

Head‐drop: A frequent feature of late‐onset myasthenia gravis

Abstract: Head-drop is a common, treatment-responsive manifestation of late-onset MG. Muscle Nerve 56: 441-444, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(32 reference statements)
0
13
0
2
Order By: Relevance
“…The diagnosis of myasthenia gravis is established by the presence of specific autoantibodies and related symptoms . Ocular symptoms are the most common symptoms, and greater than 50% of patients present with ptosis or diplopia, but the neck and limb muscles can also be involved . Respiratory muscle weakness is considered the most fatal symptom among the reported symptoms of myasthenia gravis …”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of myasthenia gravis is established by the presence of specific autoantibodies and related symptoms . Ocular symptoms are the most common symptoms, and greater than 50% of patients present with ptosis or diplopia, but the neck and limb muscles can also be involved . Respiratory muscle weakness is considered the most fatal symptom among the reported symptoms of myasthenia gravis …”
Section: Discussionmentioning
confidence: 99%
“…It can be associated with or contribute to respiratory muscle weakness. Dropped head can be the presenting sign of only sign of MG. One retrospective study, 35 including 146 patients with generalized MG showed 15 patients (10%) of the patients developed head drop. Of these 15 patients, acetylcholine receptor binding antibodies (AchR Ab) were positive in 14, and anti- MuSK antibodies positive in 1.…”
Section: Dhs In Neuromuscular Junction Disordersmentioning
confidence: 99%
“…Of these 15 patients, acetylcholine receptor binding antibodies (AchR Ab) were positive in 14, and anti- MuSK antibodies positive in 1. 35 Dropped head symptoms in MG patients with positive AchR Ab improved with treatments, but the patient with positive anti-MuSK Ab was refractory to multi treatments including prednisone, plasmapheresis, and mycophenolate mofetil. Shortcoming of the study was no imaging, EMG or muscle biopsies findings were reported.…”
Section: Dhs In Neuromuscular Junction Disordersmentioning
confidence: 99%
“…La diplopía es la forma de inicio en el 50% de los pacientes [14]. Otros síntomas son disfagia o fatiga al masticar, voz nasal, ptosis palpebral, debilidad muscular proximal, pérdida de la sonrisa y cabeza caída [15]. Los reflejos osteotendinosos son normales y nunca se compromete la pupila [16].…”
Section: Miastenia Gravisunclassified